PELAKSANAAN URUSAN PEMERINTAHAN BIDANG PERHUBUNGAN (SUB BIDANG TRANSPORTASI UDARA) DI KABUPATEN KARIMUN TAHUN 2018 - Venny Alfianita; Baskoro Wicaksono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Karimun Regency is a national strategic area in the form of the Indonesian sea border area and a free trade area and port. This is the background of the importance of regional development efforts. One of the efforts is to have adequate transportation facilities and supporting infrastructure because the presence of the airport is very important to encourage monetary growth and tourism for the growth of Karimun Regency. The interests and needs of the community for representative air transportation continue to increase, while the available aircraft are unable to meet the needs of the community due to very few routes and flight schedules. This must be a serious concern from both the central and regional governments. Then the authors sees the implementation of government affairs in transportation sector (sub-field of air transportation) in Karimun Regency in 2018.The purpose of this study is to find out how the implementation of government affairs in the transportation sector (air transportation sub-sector) in Karimun Regency in 2018. This study used a qualitative approach with descriptive methods. In collecting data, the writer used interview and documentation techniques.The results of this study are the implementation of government affairs in transportation sector (sub-field of air transportation) in Karimun Regency carried out by the Central Government namely the Ministry of Transportation through the Directorate General of Civil Aviation which is authorized to regulate, control and supervise in transportation activities namely airport standardization, airport order and the environment, airport infrastructure and airport operations and services. Whereas the Regional Government has the authority to issue permits to construct buildings for helicopter / airplane takeoffs, specifically Raja Haji Abdullah Airport.Keywords : Implementation of Transportation Affairs, Arrangement, Controlling